The effects of Pueraria mirifica extract, diadzein and genistein in testosterone-induced prostate hyperplasia in male Sprague Dawley rats - Mohamad, Jamaludin; Masrudin, Siti Saleha; Alias, Zazali; Muhamad, Nur Airina (Springer, 2019)
Pueraria mirifica (PM) is a medicinal plant native to Thailand contained high amount of phytoestrogen and possesses anticancer activity. This study reports the effect of P. mirifica extract, phytoestrogen of diadzein and genistein for its benign prostate hyperplasia properties in testosterone-induced prostate hyperplasia in male Sprague Dawley rats. The P. mirifica extract was evaluated for its total phenols, flavonoid and antioxidant activity using DPPH, FRAP and metal chelating assay. The assessment of P. mirifica, diadzein and genistein against benign prostate hyperplasia was determined in testosterone-induced prostate hyperplasia in male Sprague Dawley rats. The total phenol was higher than flavonoid but showed low antioxidant activity of DPPH, FRAP and metal chelating. The aqueous PM extract at 1000 mg/kg significantly increased testosterone levels in testosterone-induced rats by 13% while diadzein and genistein increased it by 11% and 17% respectively. However, levels of FSH, LH, triglyceride and HDL are not affected by the oral administration of PM, diadzein and genistein to the rats. Similarly, total protein, albumin, globulin, total bilirubin, conjugated bilirubin, alkaline phosphatase, alanine aminotransferase, AST, and G-glutamyltransferase showed no significant difference as compared with negative control rats. The body weight of the rats, testis, kidney and liver showed no toxic effect. The zinc content increased significantly and the zinc transporter gen of ZnT4 and ZIP4 highly expressed suggesting that the PM, diadzein and genistein plays essential role in modulating prostate zinc homeostasis. Similarly, the expression of IL-6, AR and ER was significantly reduced indicating functioning in regulation of prostate growth and acts as anti-inflammatory role in preventing BPH. In conclusion, the results indicated that PM reduced BPH and contributed to the regulation in the zinc transport expression of the prostate cells in the benign prostate hyperplasia (BPH). © 2019, Springer Nature B.V.